Comparison of Complications between Total and Subtotal Thyroidectomy in Simple Multinodular Goitre - Ahmed, Nadim; Ahmad, Sami; Ahmed, Farhad Uddin; Hossain, Muhammad Anwar; Saha, Krishna Pada; Bin Aziz, Nur Mohammod Sayed; Hassan, Mohammad Rashedul (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Multinodular goitre is one of the most common endocrine surgical problems. Because controversy still continues to surround the use of total thyroidectomy for management of simple nodular goitre, the present study was conducted to compare the complications between total and subtotal thyroidectomy for management of simple multinodular goitre. Materials & methods: The experimental study was conducted in the department of Surgery and ENT, Rajshahi Medical College Hospital over a period of 2 years from July 2011 to June 2013. Of the total 83 simple multinodular goitre patients – 38 were assigned to total and 45 to subtotal thyroidectomy groups. Student’s t-test was done to analyze the means of quantitative variables & Chi-square (X2) and Fisher Exact test was applied to analyze categorical variables. Results: Most (88.9%) of patients in subtotal thyroidectomy (STT) group and 86.8% in total thyroidectomy (TT) group did not receive any blood transfusion during operation. Only 1(2.2%) patient in STT group experienced significant intraoperative haemorrhage. All patients were successfully operated. However, few patients of either group experienced some complications. Tetany was developed in 7.89% patients of TT and 4.44% patients of STT group. The other complication was recurrent laryngeal nerve (RLN) palsy (5.3% in TT and 2.2% in STT groups). No case of postoperative haemorrhage (haematoma) or wound infection was occured in either group. In TT group 5 (13.16%) patients and in STT group 4 (8.89%) patients developed different complications with no significant difference between the groups (p=0.533). The mean postoperative hospital stay was higher in TT group than In STT group (6.21 ± 0.99 vs. 5.96 ± 0.79 days), though the difference is not statistically significant (p= 0.206). Conclusions: The study shows that total thyroidectomy can be performed without increasing risk of complications and is a better alternative to subtotal thyroidectomy for the treatment of simple multinodular goitre. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 55-59